Wideband PIFA antenna for higher LTE band applications (2015)
This paper introduces a broadband planar inverted-F antenna (PIFA) with U–Shaped capacitive feed technique for higher LTE band applications. The proposed antenna is based on a simple PIFA, where the capacitive feed plate, radiating plate and ground plate is modified into a U–Shaped such that the antenna can have wideband characteristics. With the use of the proposed feeding configuration, the antenna shows a very wide pattern and impedance bandwidth of about 81.6% for VSWR ≤ 2.0 from 1.66 GHz to 3.95 GHz which can cover the higher band of LTE (1.71GHz-3.8GHz), DCS 1800, DCS 1900, UCDMA, UMTS, IMT 2000, DMB, Wi-Fi, 2.4GHz, WiMAX (2.3–2.5 GHz), WiMAX (3.4–3.5 GHz) and Bluetooth applications.